2019
DOI: 10.1111/jpc.14575
|View full text |Cite
|
Sign up to set email alerts
|

How parents use, search for and appraise online health information on their child's medical condition: A pilot study

Abstract: Aim The internet has rapidly developed to become a default information source for parents when searching for information about their child's medical condition. This study aims to understand how parents use, search for and appraise the relevance and credibility of online information relating to children's health. Methods This research involved a practical task with parents of in‐patients with subacute health conditions at The Children's Hospital at Westmead. Each was presented with a scenario detailing symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 28 publications
(99 reference statements)
5
45
2
Order By: Relevance
“…While participants in the current study regularly used the Internet for information seeking, they were often frustrated by the quality, reliability, and relevancy of information. This finding was not unexpected as the literature has commonly shown that online health information differs significantly in reliability and accuracy (Benedicta et al, 2019;Jaks et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…While participants in the current study regularly used the Internet for information seeking, they were often frustrated by the quality, reliability, and relevancy of information. This finding was not unexpected as the literature has commonly shown that online health information differs significantly in reliability and accuracy (Benedicta et al, 2019;Jaks et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…With unmet information needs, families increasingly seek out other sources of information, such as the Internet, to fill gaps in knowledge. However, parents often become frustrated by the lack of reliable and trustworthy information resources (Benedicta et al, 2019;Dol et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Parents were found to have personal preferences for certain types of websites and their content. 21 23 26-28 31-42 Parents reported often favouring certain websites over others, which included official health information 25 To explore parents' experiences and perspectives of having a baby who needs early abdominal surgery; identify the questions and problems that matter to parents during and after their pregnancy and infant's surgery and identify the long-term impact on parents and families.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…'I think it allows you to then make a decision on how serious something might be or whether you need to take action straight away or if it's something that you can potentially wait up and see what happens.' 21 (Subacute conditions, think aloud and interview study)…”
Section: (Various Conditions Including Cystic Fibrosis Metabolic Conmentioning
confidence: 99%
See 1 more Smart Citation